Adaptive protection coordination scheme against the staircase fault current waveforms in PV‐dominated distribution systems. Issue 9 (26th March 2018) - Fani, Bahador; Dadkhah, Mohammad; Karami‐Horestani, Alireza
Abstract : Photovoltaic (PV) systems, as distributed energy resources, can adversely affect the coordination of the protection system in distribution circuits. Various approaches have been presented in the literature to solve this problem, but none of them has proposed a solution for the staircase current waveforms seen in PV‐dominated distribution systems. As there is insufficient time to apply new settings to a protection device following a fault, the appropriate solution should be to adaptively modify the characteristic curves in advance of the fault. Accordingly, using the voltage profile as a pre‐fault index for current waveform, this study suggests an adaptive approach to efficiently modify the protection settings before the fault occurrence. To this end, first, an offline technique is used to calculate the best appropriate group setting corresponding to each voltage profile. Second, in real time and according to the voltage profile, an online algorithm applies the predefined group settings to the corresponding protection devices. Simulation results demonstrate the effectiveness of the proposed method on a practical network such that by applying the proposed technique, settings on programmable protection devices can be readily modified to improve on their coordination.